Increasing incidence of pediatric mild traumatic brain injury in Finland – a nationwide register study from 1998 to 2018. Issue 2 (February 2023) - Kuitunen, Ilari; Ponkilainen, Ville T; Iverson, Grant L; Isokuortti, Harri; Luoto, Teemu M; Mattila, Ville M
Highlights: The overall incidence of pediatric traumatic brain injury increased by 118% from 1998 to 2018 in Finland. Most of this was due to an increase in mild injuries (concussions), which had more than a two-fold increase from 2010 to 2018. Boys had a higher incidence of traumatic brain injuries in all age groups. Abstract: Aim: The purpose of this study is to document the annual incidence and incidence trends of pediatric traumatic brain injury (pTBI) in Finland over the course of 21 years. Methods: We conducted a retrospective nationwide register-based cohort study and used the Finnish Care Register and Population information statistics from 1998 to 2018. The patient group includes all patients aged <18 at the time of injury. We included all emergency department (ED) visits and subsequent inpatient admissions (meaning at least one night in the hospital) with International Classification of Diseases diagnostic code S06*. We calculated pTBI incidences per 100, 000 person-years with 95% confidence intervals and the incidences were compared by incidence rate ratios (IRR), including age, diagnosis, and gender stratified analyses. Results: A total of 71, 972 patients were included with 76, 785 ED visits or hospitalizations for pTBI diagnoses. The annual incidence of diagnosed pTBI was 251 (CI: 241–260) per 100, 000 in 1998 and 547 (CI: 533–561) per 100, 000 in 2018, indicating a 118% increase in the incidence (IRR 2.18 CI: 2.09–2.28). Boys had 32% higher incidence (IRR 1.32 CI: 1.30–1.34) than girls. The highest cumulative incidence was observed among boys aged <1 years, 525 (CI: 507–543) per 100, 000, and boys had higher incidences in all age groups. The most used diagnostic code was concussion, which included 92.1% of the diagnoses followed by diffuse brain injury, which included 2.3% of the diagnoses. The increase in the incidence of diagnosed pTBI was notably high after 2010. Concussion diagnoses and pTBI cases that were discharged directly from the ED had more than a two-fold increase from 2010 to 2018, whereas the incidence of inpatient admissions for pTBI increased by 53%. Conclusions: The overall incidence of diagnosed pTBI has increased in Finland especially since 2010. Boys have higher incidence of diagnosed pTBI in all age groups. Most of the increase was due to increase in the concussion diagnoses, which may be due to the centralization of EDs into bigger units and increased diagnostic awareness of mild pTBI.